Clinical efficacy evaluation of washed microbiota transplantation treatment for metabolic related fatty liver disease and its impact on tongue coating microorganisms - Huang, Lingui; Wang, Siqi; Zhang, Hao; Feng, Shuo; Zhong, Haojie; Chen, Junyi; Xie, Wenrui; Wu, Lei; Zhang, Tiantian; He, Xingxiang; Yang, Juan (Frontiers in Endocrinology, 2025)
ObjectiveThe present study aims to explore the impact of washed microbiota transplantation (WMT) on the tongue microbiota composition of individuals with metabolic-associated fatty liver disease (MAFLD) and elucidate its biological correlations.MethodsWe conducted a comprehensive analysis of hepatic fat deposition and characterized the tongue coating microbiota using 16S rRNA gene sequencing in MAFLD patients before and after undergoing WMT treatment. Furthermore, a MAFLD mouse model was established for additional validation.ResultsAt the genus level, significant differences in tongue coating microbiota structure were observed between MAFLD patients and HC. Specifically, Neisseria positively correlated with the BARD score, Porphyromonas and Rhodococcus positively correlated with fat decay, and Petostreptococcus, a conditionally pathogenic bacterium, exhibited a significantly higher relative abundance in MAFLD patients compared to HC. Conversely, Actinomyces positively correlated with the FIB-4 score, Megasphaera negatively correlated with the APRI score, and Subdoligulum negatively correlated with low-density lipoprotein levels. Notably, following effective WMT treatment, patients exhibited improved symptoms, with a significant reduction in the relative abundance of Petostreptococcus and an increase in potential probiotics such as Lachnospiraceae and Bifidobacterium in their tongue coating microbiota. Additionally, structural differences in the tongue coating microbiota were identified at the genus level between MAFLD model mice and HC mice. After WMT treatment, the relative abundance of conditionally pathogenic bacteria like Enterococcus was significantly decreased in MAFLD model mice.ConclusionsWMT not only significantly ameliorates liver fat deposition in MAFLD patients but also alters the tongue coating microbial structure associated with disease severity, thereby potentially mitigating adverse patient outcomes.